Estudio de mercado de la panela en el cantón Loja - Cango Paz, José Luis (2014)
The research work entitled "STUDY OF THE BROWN SUGAR IN THE CANTON MARKET LOJA" was held in Loja canton, the objectives of this study are intended to analyze the behavior of the demand the parishes of this canton and in relation to the offer, identify more representative of Vilcabamba and Malacatos parishes producers in order to meet the technical implicationsquality, quantity and price of it; Likewise determine the different marketing channels. This study was used to 384 surveys consumer of panela, the sample size that turned out to be according to the 2010 census, projected to 2014, which rests in the INEC where the total number of inhabitants in the urban area of the city of Loja is 189.131, whereas the number of individual average of 4.68; determined 40.240 families within the city of Loja; In addition surveys was applied to most representative panela producers including identified a total of 11; in 8 Malacatos and 3 Vilcabamba. The surveys found an average of annual 8202 panelas 1 pound block of panela consumption, then the analysis of supply 11 brown sugar producers, was 32,500 blocks 1 lb panela weekly sales average, that multiplied by 4 gives a result of 130,000 monthly; annual and a total of 1' 560.000; and the sale of brown sugar in the city of Loja is 18% means an average of 280,000 panelas's block of 1 pound, this product generally offer an average of 0.30 cents. Costs were calculated for the production of 900 panelas's block of a pound a pound which is the product of two tasks of cane, being the amount of 285.85 dollars and revenues of 284.40 dollars, with a net income of 25.55 with a return of 10% resulting in a benefit cost of 1.09 dollars. i.e. for every dollar of investment generated a profit 9 cents. It is justified from the financial point of view since it would cover the costs of production generated. The unsatisfied demand turned out to be 1 pound block panelas 1.177.468. Plaintiffs requirements and according to the surveys applied to the families of the canton of Loja and leaning on the marketing mix, product, price, place, promotion, is the relevant recommendations in order to offer an excellent product presentation undergo a rigorous control of the quality according to the requirements of the market.